Phihlippine High School of Arts and Technology - Mercado, Alyanna Moira C.; Yazon, Rizalino (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
In recent years, priority has been given o STEM subjects, leaving the arts in the backseat of the academe. This has resulted to the Filipino's lack of cultural awareness, appreciation for the arts, and the possibilities of developing creative industries (DLSU, 2015). While other countries have better access to arts education, the Philippines only has one secondary school solely dedicated to the arts, the Philippine High School for the Arts (PHSA). Its campus is located in Los Banos, Laguna and was founded in 1978. Despite the rising number of applicants in recent years, they can only accept 40 to 60 new students every year of 10% of their applicant population. Therefore, there should be a need to build a new PHSA campus in order to accommodate more artistically gifted high school students, as well as to promote and strengthen the presence of art education in the country today. It will suitably serve the learning needs of the 21st century and it can also serve as a prototype for similar institutions to be established in the future. This thesis seeks to provide a high school for the arts built for 21st century learners. It emphasizes on providing spaces that encourage interaction and informal learning within its students from various art courses. It aims to create an effective learning environment by highlighting the importance of collaboration, personalization, and student empowerment in the arts.
include appendices
Quezon City
Keywords: Art -- Study and teaching -- Philippines. -- Curricula